Environmental impact (El) of anthropic activity in six awajun native communities in the province of Bagua, Amazonas, Peru, 2019 - Beltrán Orbegoso, Raúl Antonio (2020)
The environmental impact (El) of anthropogenic activity in communities originating in the Amazon region is little known; in that sense, the objective of the research was to identify the El of anthropic activity in six native Awajun communities from the Amazon region of Peru, in 2019. The study is exploratory and descriptive. The El was determined using Leopold's two-way matrix (as modified by Beltran, 2005), which considers in its columns the five most important anthropic activities identified in communities: inadequate solid waste management, destruction ofthe slope and soil ofthe Marañón River, uncontrolled extraction ofGuadua angustifolia "bamboo", construction of ponds for family fish farming and intense cultivation ofTheobroma cacao "cacao" and Oriza sativa "rice"; and in its ranks, to the thirteen most notorious environmental impacts, observed in the communities. Five criteria were measured: duration, extent, intensity, reversibility and total magnitude; the overall environmental impact was ultimately assessed. The five anthropic activities were found to have the greatest negative impacts (-5 .0 and -4.4) on the loss of schooling and soil structure; on the other hand, anthropic activities have a positive impact ( 4.8) on the generation ofunderemployment.